1991
DOI: 10.1093/clinchem/37.10.1708
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the measurement of protein S in plasma

Abstract: The anticoagulant factor Protein S circulates in two major forms, free and bound to C4b binding protein (C4BP). We report a monoclonal antibody-based enzyme-linked immunosorbent assay of human Protein S that is sensitive (detection limit 30 ng) and free of notable competition from other vitamin K-dependent proteins. We demonstrate assay sensitivity to Protein S-C4BP complex, as well as to free Protein S by (a) results of immunoaffinity chromatography involving the assay antibody; (b) parallelism between the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…An early study using gel‐filtered bovine plasma suggested that there were three forms of PS in addition to PS–C4BP complexes [27]. In another study, most of the free PS in human plasma had an apparent mass of dimers during gel filtration, although conformational considerations could apply [28]. These are in partial agreement with our finding that free plasma PS consists of monomers and multimers.…”
Section: Discussionsupporting
confidence: 89%
“…An early study using gel‐filtered bovine plasma suggested that there were three forms of PS in addition to PS–C4BP complexes [27]. In another study, most of the free PS in human plasma had an apparent mass of dimers during gel filtration, although conformational considerations could apply [28]. These are in partial agreement with our finding that free plasma PS consists of monomers and multimers.…”
Section: Discussionsupporting
confidence: 89%
“…All assays were performed in the investigators' laboratories either by ELISA: FV antigen [coefficient of variation (CV) 5.8%][21], FVIII antigen (CV 7.8%), FIX antigen (CV 10%), VWF (CV 3%) [22], protein Z (CV 6.5%) [24], ZPI (CV 7.2%) [24], APC–α1AT complex (CV 12.4%) [25] and APC–PCI complex (CV 11.7%) [25], or radioimmunoassay: prothrombin (CV 8%) [26], antithrombin (CV 5%) [27,28], protein S (CV 9.8%) [29], F1.2 (CV 8%) [28], PCP (CV 14%) [28] and FPA (CV 8%) [28], the Clauss method for fibrinogen (CV 1.7%) [30,31] using the ST4 instrument (Diagnostica Stago, Parsipanny, NJ, USA), a clot‐based functional assay for protein C: (CV 5.5%) [20,23] or micro latex bead agglutination for d ‐dimer (CV 9.2%) (Biomerieux, Durham, NC, USA) [32,33].…”
Section: Methodsmentioning
confidence: 99%
“…The assays for factor VIIc (CV = 5.3%), factor VIIag (CV = 6.0%), factor VIIIc (CV = 9.7%), factor IXc (CV = 5.8%), factor Xc (4.7%), fibrinogen (CV = 2.9%), tissue factor pathway inhibitor (TFPI; CV = 9.5%), antithrombin-III (AT-III; CV = 4.5%), protein C antigen (CV = 2.5%), total protein S (9.9%), free protein S (CV = 6.7%), factor XIa-␣ 1 -anti-trypsin complex (FXIa-␣ 1 -AT; CV = 6.1%), C-reactive protein (CRP; CV = 8.9%), prothrombin fragment 1-2 (F1-2; CV = 8.5%), fibrinopeptide A (FPA; CV = 8.4%), fibrin fragment D-dimer (CV = 7.0%), ␣ 1 acid glycoprotein (CV = 7.0%), plasminogen (CV = 3.6%), tissue plasminogen activator (tPA; CV = 7.0%), plasminogen activator inhibitor-1 (PAI-1; CV = 8.4%), plasmin-␣ 2 -antiplasmin (PAP; CV = 3.0%), and tPA/PAI complex (CV = 14.3%) have been previously described (4,30,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47).…”
Section: Antigen Levelsmentioning
confidence: 95%